2016
DOI: 10.1007/s12149-016-1118-3
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-gated time-of-flight PET/CT during whole-body scan for lung lesions: feasibility in a routine clinical setting and quantitative analysis

Abstract: Respiratory gating during whole-body scan in routine TOF PET/CT examinations is feasible and can reduce both misregistration and PET image blurring, and improve the SUVmax of lung lesions located primarily in the LL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These results are consistent with previous studies assessing respiratory gating. Indeed, authors reported an increase of the value of SUVmax ranging from 7 to 159% for lung lesions, especially for lung cancer ( 14 18 ). In our study, increase value of SUVmax ranged from −19 to 168%.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies assessing respiratory gating. Indeed, authors reported an increase of the value of SUVmax ranging from 7 to 159% for lung lesions, especially for lung cancer ( 14 18 ). In our study, increase value of SUVmax ranged from −19 to 168%.…”
Section: Discussionmentioning
confidence: 99%
“…They reported smaller tumour volumes on 4D PET/CT than at 3D PET/CT but with motion freeze demonstrating significantly smaller volumes than both 3D and 4D PET/CT. Suzawa et al studied the use of respiratory gated time of flight (TOF) PET/CT in the analysis of lung lesions [26]. The principle of TOF PET/CT is that instead of traditional PET/CT where the annihilated positron can be located to a line of response the location can be more accurately located along this line due to calculating the times of arrival of the two 511KeV photons.…”
Section: I) Impact On Gtvmentioning
confidence: 99%
“…Two in-house experienced radiologists who are specialized in nuclear medicine were invited to perform image assessments; if there is any uncertainty, consensus between two radiologists was required. Lesions with SUV max < 1.0 were considered as non-malignant lesions and discarded from downstream analysis; this threshold value was chosen based on previous studies ( 27 , 28 ). The use of the SUV threshold in tumor volume segmentation eliminates intra-rater and inter-rater segmentation variability, and it is worth noting that all the generated segments in this study were approved by experienced medical oncologists with specialty in nuclear medicine.…”
Section: Methodsmentioning
confidence: 99%